2006
DOI: 10.1128/aac.50.1.318-323.2006
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Design of Agents That Inhibit the cep Quorum-Sensing System of Burkholderia cenocepacia

Abstract: Recent research has provided evidence that interference with bacterial cell-to-cell signaling is a promising strategy for the development of novel antimicrobial agents. Here we report on the computer-aided design of novel compounds that specifically inhibit an N-acyl-homoserine lactone-dependent communication system that is widespread among members of the genus Burkholderia. This genus comprises more than 30 species, many of which are important pathogens of animals and humans. Over the past few years, several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 28 publications
(38 reference statements)
0
20
0
Order By: Relevance
“…However, a number of reports of identification of structurally distinct non-AHL analogous molecules as QS inhibitors (Müh et al, 2006;Sabbah et al, 2012;Riedel et al, 2006;Park et al, 2006;Degrassi et al, 2002;Jadhav et al, 2011) which bind with the receptor in a non-competitive fashion and thus retards QS signalling. These categories include inhibitors carrying non-AHL core of tetrazole (Müh et al, 2006), thiophene (Riedel et al, 2006), cyclic dipeptides (2,5 diketopiperazines) (Park et al, 2006;Degrassi et al, 2002), novel triphenyl scaffold (Campbell et al, 2009) and some small molecules with electrophilic functionalities (isothiocyanates, haloacetamides, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a number of reports of identification of structurally distinct non-AHL analogous molecules as QS inhibitors (Müh et al, 2006;Sabbah et al, 2012;Riedel et al, 2006;Park et al, 2006;Degrassi et al, 2002;Jadhav et al, 2011) which bind with the receptor in a non-competitive fashion and thus retards QS signalling. These categories include inhibitors carrying non-AHL core of tetrazole (Müh et al, 2006), thiophene (Riedel et al, 2006), cyclic dipeptides (2,5 diketopiperazines) (Park et al, 2006;Degrassi et al, 2002), novel triphenyl scaffold (Campbell et al, 2009) and some small molecules with electrophilic functionalities (isothiocyanates, haloacetamides, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…These categories include inhibitors carrying non-AHL core of tetrazole (Müh et al, 2006), thiophene (Riedel et al, 2006), cyclic dipeptides (2,5 diketopiperazines) (Park et al, 2006;Degrassi et al, 2002), novel triphenyl scaffold (Campbell et al, 2009) and some small molecules with electrophilic functionalities (isothiocyanates, haloacetamides, etc.) (Amara et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic compounds modeled on the natural AHLs were evaluated for both their inducing activity and their ability to competitively inhibit the action of AHL in Vibrio fischeri, Burkholderia cenocepacia, and Pseudomonas aeruginosa (1,3,13,22,24,28,29). Halogenated furanones, produced by the red alga Delisea pulchra, inhibit quorum sensing in a number of bacteria (4,5,9,20,21).…”
mentioning
confidence: 99%
“…This indicated that these furanone derivatives are highly toxic to the bacteria since genetic analysis shows that a functional QS system is not required for biofilm formation in vitro. Since the discovery of the halo-furanones, a number of papers have reported on synthesis of QSI compounds by means of organic chemistry approach (Borlee et al 2008;Geske et al 2007Geske et al , 2008aMattmann et al 2008;Muh et al 2006;Olsen et al 2002;Persson et al 2005a, b;Riedel et al 2006). However, a detailed overview of this is not the scope of this chapter.…”
Section: Interference With Bacterial Gossip and Why It Work As And Amentioning
confidence: 99%